Making Sense of Corporate Social Responsibility and Work - Seivwright, Ami N.; Unsworth, Kerrie L. (Frontiers in Psychology, 2016)
Employees can be a driving force behind organisational corporate social responsibility (CSR) efforts, yet the vast majority of literature has focused on firm-level understanding and implementation of CSR. Recent literature that explores the relationship between employees and CSR has not investigated how employees conceive of their role in CSR. We propose that in order to understand the factors that affect employee engagement in CSR, we must first understand how employees conceptualise the phenomenon of CSR and how that conceptualisation fits into their work. Our exploratory, inductive study interviews two cohorts of employees, one in a not for profit and the other in a corporate organisation, revealing stark contrasts in how the different cohorts conceptualise and engage in CSR, particularly with regards to how CSR contributes to meaningfulness at work. Implications for organisations are discussed.